(untitled) (mathematica didactica, 2002)
The paper offers two pragmatical models for the furtherance of mathematically interested and especially gifted children in grades 2–4. A discussion of useful tasks and possible solutions follows, also a description of demands and requirements for tutors of such mixed groups is added, related to the special characteristics of these children.